The Function of Politeness of Teacher Language In Implementing Character Values To The Primary School Students - Dina Mardiana; Iwan Fauzi; Leli Nisfi Setiana (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2022)
This research aims to identify the function of the language politeness of the teacher in implanting character values to students in the primary school. The research was carried out at the primary school of SD Muhammadiyah Pahandut, Kota Palangka Raya. A qualitative method was used in this research with a pragmatics research design. The pragmatics design used to analyze the data was based on the principle of politeness which included six maxims and five components of speech situation. The data were obtained from conversational discourse between teachers and students containing language politeness in teaching and learning activities at the school. Then the data were also supported by doing interviews with involved teachers and by reviewing assessment report documents of students to relate the function of the teacher's language politeness with student character values of being attained. The data obtained using the triangulation technique were analyzed and presented by the qualitative descriptive technique. The results showed that there were 150 items of teacher language politeness which provided very good functions in implanting character values to students as an effort to build character for primary school students